Communicable Diseases (Including COVID-19)—Induced Global Depression: Caused by Inadequate Healthcare Expenditures, Population Density, and Mass Panic - Anser, Muhammad Khalid; Yousaf, Zahid; Khan, Muhammad Azhar; Sheikh, Abdullah Zafar; Nassani, Abdelmohsen A.; Abro, Muhammad Moinuddin Qazi; Zaman, Khalid (Frontiers in Public Health, 2020)
Coronavirus (COVID-19) is spreading at an enormous rate and has caused deaths beyond expectations due to a variety of reasons. These include: (i) inadequate healthcare spending causing, for instance, a shortage of protective equipment, testing swabs, masks, surgical gloves, gowns, etc.; (ii) a high population density that causes close physical contact among community members who reside in compact places, hence they are more likely to be exposed to communicable diseases, including coronavirus; and (iii) mass panic due to the fear of experiencing the loss of loved ones, lockdown, and shortage of food. In a given scenario, the study focused on the following key variables: communicable diseases, healthcare expenditures, population density, poverty, economic growth, and COVID-19 dummy variable in a panel of 76 selected countries from 2010 through 2019. The results show that the impact of communicable diseases on economic growth is positive because the infected countries get a reap of economic benefits from other countries in the form of healthcare technologies, knowledge transfers, cash transfers, international loans, aid, etc., to get rid of the diseases. However, the case is different with COVID-19 as it has seized the whole world together in a much shorter period of time and no other countries are able to help others in terms of funding loans, healthcare facilities, or technology transfers. Thus, the impact of COVID-19 in the given study is negatively impacting countries' economic growth that converts into a global depression. The high incidence of poverty and social closeness increases more vulnerable conditions that spread coronavirus across countries. The momentous increase in healthcare expenditures put a burden on countries' national healthcare bills that stretch the depression phase-out of the boundary. The forecasting relationship suggested the negative impact of the coronavirus pandemic on the global economy would last the next 10 years. Unified global healthcare policies, physical distancing, smart lockdowns, and meeting food challenges are largely required to combat the coronavirus pandemic and escape from global depression.